FROM SIMPLE BOOKKEEPING TO SAK: ACCOUNTANT IDENTITY CONFLICTS IN MSMES UNDERGOING DIGITAL TRANSFORMATION - Wulandari Hardjanti; Miya Dewi Suprihandari; Mochamad Ardi Setyawan (JAT : Journal Of Accounting and Tax, 2026)
Digital transformation has encouraged Micro, Small, and Medium Enterprises (MSMEs) to shift from simple bookkeeping practices toward the implementation of Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). This study aims to explore how accountants, business owners, and financial staff interpret changes in their professional roles during the digital transformation of accounting practices. The research employed a qualitative interpretive approach using a phenomenological method to understand participants’ subjective experiences. The findings indicate that the transition from traditional bookkeeping to a standards-based digital accounting system creates tensions between the established identity of transaction recorders and the emerging identity of strategic information providers. Identity conflicts are reflected in technology resistance, anxiety related to competency development, uncertainty regarding new responsibilities, and shifts in knowledge authority from practical experience to digital and accounting expertise. However, the adaptation process is supported by training programs, digital literacy enhancement, and professional mentoring, enabling individuals to develop more adaptive, collaborative, and data-oriented professional identities. The study contributes to the literature by emphasizing the social and professional dimensions of accounting digitalization in MSMEs and highlights that successful digital transformation depends not only on technological readiness but also on the reconstruction of professional identity within a changing business environment.